The marble façade of the Ducal Palace of Vila Viçosa in the context of the 1940 Centenary Commemorations: cleaning and consolidation - Soares, Clara Moura (2022)
The main goal of the present article is to study the cleaning and consolidation of the marble façade of the Ducal Palace of Vila Viçosa during the 1940s. The research was based on the archival documentation of the former Directorate-General for National Buildings and Monuments (DGEMN), which was crucial for uncovering the history and theory of conservation and restoration of monuments in Portugal since 1929, and allowed to identify protagonists as well as techniques, materials, and intervention criteria. The analysis of the choices that were made — based on principles such as minimal intervention, respect for the history of the monument through its various phases, and preservation of the patina of time — demonstrates that there was an obvious regard for the principles established by the Athens Charter (1931). Such principles are evidence of a departure from the DGEMN action paradigms at the time, which favoured restoration over conservation and defended the prevalence of a “style unity”, while sacrificing certain eras of the monuments’ past.